2017
DOI: 10.1002/bies.201600157
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing switches: Important players in cell differentiation

Abstract: Alternative splicing (AS) greatly expands the coding capacities of genomes by allowing the generation of multiple mature mRNAs from a limited number of genes. Although the massive switch in AS profiles that often accompanies variations in gene expression patterns occurring during cell differentiation has been characterized for a variety of models, their causes and mechanisms remain largely unknown. Here, we integrate foundational and recent studies indicating the AS switches that govern the processes of cell f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 78 publications
1
67
0
1
Order By: Relevance
“…We focused our analysis on the 2,633 events that involved cassette exons, and of these 2,346 (89.1%) corresponded to increased skipping (Fig 5b, binomial test, p-value<0.001). These results are consistent with previous studies which have demonstrated exon skipping following depolarisation in individual examples (An & Grabowski 2007), (Lee et al 2007), (Schor et al 2009), (Liu et al 2012), (Fiszbein & Kornblihtt 2017), but to the best of our knowledge we provide the first genome-wide analysis demonstrating widespread exon skipping (Fig 5b). Interestingly, we found an enrichment for differential splicing events with G4 motifs at the associated splicing sites, exceeding that which was expected by the background distribution (Fig 5a, c, chi-squared test with multiple testing correction, p-value<0.001, odds-ratio=1.57).…”
Section: Dynamic Splicing Responses To Stimuli Are Associated With Prsupporting
confidence: 93%
“…We focused our analysis on the 2,633 events that involved cassette exons, and of these 2,346 (89.1%) corresponded to increased skipping (Fig 5b, binomial test, p-value<0.001). These results are consistent with previous studies which have demonstrated exon skipping following depolarisation in individual examples (An & Grabowski 2007), (Lee et al 2007), (Schor et al 2009), (Liu et al 2012), (Fiszbein & Kornblihtt 2017), but to the best of our knowledge we provide the first genome-wide analysis demonstrating widespread exon skipping (Fig 5b). Interestingly, we found an enrichment for differential splicing events with G4 motifs at the associated splicing sites, exceeding that which was expected by the background distribution (Fig 5a, c, chi-squared test with multiple testing correction, p-value<0.001, odds-ratio=1.57).…”
Section: Dynamic Splicing Responses To Stimuli Are Associated With Prsupporting
confidence: 93%
“…During alternative splicing the order of exons can be varied to generate multiple different transcripts and proteins from one gene (Soller 2006;Nilsen and Graveley 2010;Fiszbein and Kornblihtt 2017). In humans, 95% of genes, and in Drosophila 63% of genes are alternatively spliced, respectively (Wang et al 2008;Fu and Ares 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative pre-mRNA splicing is a ubiquitous posttranscriptional regulatory mechanism that controls gene expression level and protein diversity in metazoan [1]. It has been well documented that alternative splicing of specific genes contributes to cell differentiation, organ development, and tissue identity [2][3][4][5]. Moreover, a large number of human diseases including congenital myotonic dystrophy and spinal muscular atrophy are caused by aberrant splicing regulation [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%